A hybrid pre-joined service network in graph database and memory for service composition. (21st May 2021) - Li, Jing; Zhang, Ming; Zhu, Ming; Cui, Lizhen; Yan, Yuhong; Song, Bowen
To make full use of the large space and persistency provided by a database and the fast processing speed of main memory, we propose a hybrid pre-joined service network method combining in-graph-database and in-memory calculations. This method firstly stores services' information and combinations in a graph database. Then, for a user's request, it retrieves candidate services from the database and constructs a service network in memory. After that, services are picked and composed to fulfil an optimal solution in memory. We assess the performance of our method by conducting experiments and comparing the approach with other database-based methods. Experiment results indicate the efficiency of this method in comparison, and it can always find solutions and lead to higher users' satisfaction.